Collaborating Blended Learning Model into Content Representation Product Design at Eleventh Grade English Subjects - Testiana Deni Wijayatiningsih; Nanda Eka Yuniarti (Universitas Dian Nuswantoro, 2019)
The design development of the CoRe (Content Representation) model is another model of the lesson plan that is applied using the Blended learning model. The purpose of this study is to design and validate the suitability of CoRe products with the high school syllabus. The method used by using descriptive quantitative method based on the stages of R and D (Research and Development), especially in seven stages, namely; research and data collection, planning, initial product development, piloting and refinement of initial products, testing and refinement of products that have been refined for final product testing, and disseminated, implemented and institutionalized. The results obtained are the valid lesson plan design plan with CoRe used in teaching English to high school class XI students. The activity of students also increased by showing a positive response and the results of the daily pre-test and post-test exercise improved well. In addition, the CoRe Model can also be used to help teachers improve Pedagogical Content Knowledge in the teaching and learning process.